Role of concrete in sustainable development proceedings of the International Symposium dedicated to professor Surendra Shah, Northwestern University, USA held on 3-4 Septemeber 2003 at the University of Dundee, Scotland, UK - Shah, S. P.; Dhir, Ravindra K.; Newlands, Moray D.; Paine, Kevin A. (Thomas Telford, 2003)
Themes outlined in this book include: mechanical properties of concrete; role of fibres in ductility and strength; durability and performance; withstanding severe conditions; specialist concrete and construction techniques; and exploiting concrete.